2020
DOI: 10.1186/s42155-020-00159-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopically-guided interventions with radiation doses exceeding 5000 mGy reference point air kerma: a dosimetric analysis of 89,549 interventional radiology, neurointerventional radiology, vascular surgery, and neurosurgery encounters

Abstract: Purpose To quantify and categorize fluoroscopically-guided procedures with radiation doses exceeding 5000 mGy reference point air kerma (Ka,r). Ka,r > 5000 mGy has been defined as a “significant radiation dose” by the Society of Interventional Radiology. Identification and analysis of interventions with high radiation doses has the potential to reduce radiation-induced injuries. Materials and methods Radiation dose data from a dose monitoring system for 19 interventional suites and 89,549 consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…It should be noted that the dose distribution associated with this data can be different from the dose distribution in each institution, using this information to predict doses above 5000 mGy may overestimate the risk in institutions where strong dose reduction measures are practiced while underestimating the risk in those institutions where weaker dose reduction measure is practiced. A subtle but important clue in this result by Bundy et al [21], that suggests that the dose distribution of that data is likely skewed to the right of our dose distribution, is that 260 cases out of 89,549 are above 5000 mGy. If we scaled our data in table 3 to 89,549 by assuming an identical dose distribution, we should expect close to 20 cases above 5000 mGy in our institution.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…It should be noted that the dose distribution associated with this data can be different from the dose distribution in each institution, using this information to predict doses above 5000 mGy may overestimate the risk in institutions where strong dose reduction measures are practiced while underestimating the risk in those institutions where weaker dose reduction measure is practiced. A subtle but important clue in this result by Bundy et al [21], that suggests that the dose distribution of that data is likely skewed to the right of our dose distribution, is that 260 cases out of 89,549 are above 5000 mGy. If we scaled our data in table 3 to 89,549 by assuming an identical dose distribution, we should expect close to 20 cases above 5000 mGy in our institution.…”
Section: Discussionmentioning
confidence: 57%
“…Bundy et al [21] reported that fluoroscopicallyguided procedures with radiation dose exceeding 5000 mGy reference point air kerma are uncommon. Based on the analysis of 89,549 patients over a six-year period from 2013 to 2019, only 260 out of 89,549 cases were above 5000 mGy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staff dose is also affected by distance from the irradiated area, as found by Sailer et al and Omar et al, who reported that operator doses during neurology procedures were lower compared to thoracic and abdominal procedures [ 38 , 39 ]. Bundy et al reported that interventional neuroradiology had the highest average AK, but that procedures exceeding 5 Gy were more likely performed by vascular surgeons, suggesting this may be due to the lack of radiation training compared to radiologists [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high exposure time during the procedure makes additional care necessary. The increase in reported severe skin lesions highlights the need for education about radiation risks and the importance of strategies to optimize exposure [6,7].…”
Section: Introductionmentioning
confidence: 99%